Point F = (-2,-3); Apply the midpoint formula, (x1+x2/2),(y1+y2/2) = (x,y).
-6+2/2
-4/2
x=-2
-2+(-4)/2
-6/2
y=-3
(x,y)=(-2,-3)
Answer:
Chris ate more of his candy bar
9514 1404 393
Answer:
(-5,1)
Step-by-step explanation:
To eliminate x, multiply the first equation by 3 and add 2 times the second equation.
3(-2x +7y) +2(3x -4y) = 3(17) +2(-19)
-6x +21y +6x -8y = 51 -38
13y = 13
y = 1 . . . . . matches the third answer choice
(x, y) = (-5, 1)
Answer:
B, g(n) = 50*1.15^n
Step-by-step explanation:
It's a geometric sequence because the money is increasing by a percentage every year.
25 add them up Your welcome